DKK1 Antagonizes Wnt Signaling without Promotion of LRP6 Internalization and Degradation - Semënov, Mikhail V. (American Society for Biochemistry and Molecular Biology, 2008)
DKK1 is a secreted protein that antagonizes Wnt signaling and plays essential roles in vertebrate embryogenesis including head induction, skeletal development, and limb patterning. DKK1 is also implicated in osteoporosis, arthritis, and cancer and represents a potential therapeutic target for the treatment of these diseases. DKK1 is a high affinity antagonistic ligand for LRP6, which is a Wnt coreceptor that acts together with the Frizzled serpentine receptor to initiate Wnt signal transduction. Two different models have been proposed to account for the mechanism by which DKK1 antagonizes LRP6 function. One model suggests that DKK1 binding to LRP6 disrupts Wnt-induced Frizzled-LRP6 complex formation, whereas the other model proposes that DKK1 interaction with LRP6 promotes LRP6 internalization and degradation, thereby reducing the cell surface LRP6 level. To clarify the molecular basis of DKK1 action, we examined how DKK1 affects the endogenous LRP6 in several mammalian cell lines including mouse embryonic fibroblasts. Here we show that DKK1 inhibits Wnt signaling but induces neither LRP6 down-regulation from the cell surface nor reduction of total LRP6 protein level and that DKK1 has no effect on the rate of continuous internalization of LRP6 and the half-life (about 4.7 h) of LRP6. We conclude that DKK1 inhibition of LRP6 is independent of LRP6 internalization and degradation.